The Role of COAR in Advancing Open Access in Africa - Shearer, Kathleen (My University, 2025)
The Role of COAR in Advancing Open Access in Africa - AfricArXiv Open Science Webinar Series 2025
This webinar session featured Kathleen Shearer, the Executive Director of the Confederation of Open Access Repositories (COAR), as our guest speaker. She spoke on the topic: The Role of COAR in Advancing Open Access in Africa In this webinar, attendees discovered: - How COAR supports open access to research in Africa. - Ways African researchers and institutions can make their work more visible worldwide. - Why collaboration and global standards are important for African repositories. - Exciting programs and opportunities COAR offers to support African research. This webinar series is co-organized by: UbuntuNet Alliance: https://ubuntunet.net/ and Access 2 Perspectives: https://access2perspectives.org/ and supported by the African Open Science Platform (AOSP) https://aosp.org.za/
Keywords: Open Science; Open Access; Research in Africa; Science Communication; Scholarly Communication; AfricArXiv; Webinar; COAR